2015
DOI: 10.2500/aap.2015.36.3859
|View full text |Cite
|
Sign up to set email alerts
|

EpiPen4Schools pilot survey: Occurrence of anaphylaxis, triggers, and epinephrine administration in a U.S. school setting

Abstract: More than one in ten schools that participated in the EpiPen4Schools survey reported an anaphylactic event. Approximately 25% of individuals with anaphylactic events were not treated with EAIs, and 20.4% of patients were not taken to the hospital after an anaphylactic event. Analysis of these data supports the value of stocking EAIs and of providing continuing education regarding the recognition and proper treatment of anaphylaxis for school personnel.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
55
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(60 citation statements)
references
References 0 publications
3
55
0
2
Order By: Relevance
“…15 The EpiPen4Schools pilot survey involving 6019 schools in the United States also revealed that an AAI was used in 74.7% of 851 anaphylaxis episodes that occurred in 607 schools over one school year from 2013 to 2014. 16 This study did not have details on the total number of students and it is difficult to compare the AAI usage rate, except to note that it is possible that in the school environment, anaphylaxis might be better recognized and an AAI used more appropriately than in the community (as compared with the UK study). However, none of these surveys has details on the number of students already at risk of anaphylaxis.…”
Section: Discussionmentioning
confidence: 96%
“…15 The EpiPen4Schools pilot survey involving 6019 schools in the United States also revealed that an AAI was used in 74.7% of 851 anaphylaxis episodes that occurred in 607 schools over one school year from 2013 to 2014. 16 This study did not have details on the total number of students and it is difficult to compare the AAI usage rate, except to note that it is possible that in the school environment, anaphylaxis might be better recognized and an AAI used more appropriately than in the community (as compared with the UK study). However, none of these surveys has details on the number of students already at risk of anaphylaxis.…”
Section: Discussionmentioning
confidence: 96%
“…Many immunologic triggers can induce an anaphylactic reaction, the most common being food, insect venom, and medication 5,2022. The rate of anaphylaxis appears to be increasing dramatically in the developed countries,23,24 which may partially be due to an increase in the prevalence of food allergies 25.…”
Section: Overview Of Anaphylaxismentioning
confidence: 99%
“…The rate of anaphylaxis appears to be increasing dramatically in the developed countries,23,24 which may partially be due to an increase in the prevalence of food allergies 25. Individuals with a previous history of allergic reactions and asthma are at the greatest risk 7,22. However, anaphylaxis can commonly occur in those with no known history of allergy,22 and triggers are never identified in many cases 2022.…”
Section: Overview Of Anaphylaxismentioning
confidence: 99%
See 1 more Smart Citation
“…21 White et al performed a cross-sectional, web-based survey of 6,019 schools participating in the EpiPen4Schools program which assessed anaphylactic events and epinephrine autoinjector (EAI) use during the 2013-2014 school year. 22 They found that greater than one in ten schools participating in the EpiPen4Schools survey reported an anaphylactic event. Of concern, ϳ25% of anaphylactic events were not treated with EAIs, and 20.4% of patients were not taken to the hospital after an anaphylactic event.…”
mentioning
confidence: 99%